The presence of self - Perinbanayagam, R. S., 1934- (Rowman & Littlefield, 2000)
Drawing on ideas from Charles Sanders Peirce, George Herbert Mead, Kenneth Burke, and Mikhail Bakhtin, this work focuses on the centrality of the social act in describing and understanding the beingness of the human individual, situating such acts in dialogic and rhetorical processes. Such processes enable actors to give presence to their selves and, it is claimed, put them into play by using both a logic and a poetic of identity.